Benzyl N-[1-(furan-2-yl)ethylidene]hydrazinecarbodithioate. - Khoo, Teng Jin; Cowley, Andrew R.; Watkin, David J.; Crouse, Karen Anne; Tarafder, M. T. H. (International Union of Crystallography, 2005)
The title compound, C14H12N2S2O, contains a dithiocarbazate group. The phenyl ring is disordered and perpendicular [dihedral angle of 48.0 (3)] to the rest of the molecule, which is planar.